Analisis Prediksi Ancaman Militer dan Pemilihan Teknologi Senjata Rudal Pada Coastal Defense Concept di Laut Natuna Utara - Wahyu Endriyanto (Rekayasa, 2023)
The military threat in the North Natuna Sea is now becoming more real and can no longer be avoided. This study aims to carry out threat forecasting analysis and selection of missile weapons technology (guided missiles) on the concept of Coastal Defense in the North Natuna Sea. This study uses the Linear Regression method using Excel to predict threats that will continue to occur within the next 5 (five) years. Furthermore, this study also uses the Analytic Hierarchy Process (AHP) method to select the most appropriate missile weapon technology to deal with threats that occur in the North Natuna Sea. The results of the study obtained a Linear Regression equation with the equation Y = 253.952561 + 7.1855428X, it can be explained that if the value is X = 0 then Y = 253.95, then the value of x is 7.186x which has a positive value, meaning the influence of the variable x is positive on variable Y. When X the military budget increases, Y (military strength/defense posture) will also increase. Furthermore, the selection of the best alternative for coastal defense missiles using the AHP method consists of four criteria for range, price, explosive power, and logistical continuity as well as the four best alternative missiles in the world, the results of the analysis selected the 3M-54E missile from Russia with a weight of 41.9 %. Â Â